Pengaruh Gaya Hidup, Harga Dan Iklan Terhadap Keputusan Pembelian Pada Aplikasi Shoope Studi Pada Mahasiswa FEBI UIN STS Jambi - Bima Bangun Mura; Nazori Majid; Addiarahman (JOURNAL SAINS STUDENT RESEARCH, 2023)
The purpose of this research was to find out and analyze the influence of lifestyle, price and advertising on purchasing decisions on the Shoope Study Application for students of the Faculty of Islamic Economics and Business, Uin Sts Jambi. In this study using quantitative methods. And the samples used in this study were 70 students. The results of this study indicate that partially, lifestyle and price have a significant negative effect on purchasing decisions, while advertising has a positive and significant effect on purchasing decisions. Simultaneously lifestyle, price, and advertising together influence purchasing decisions.